Case study about contamination of soil and groundwater for benzene in the region of Barueri (SP) - Calza, Andressa; Mata-Lima, Herlander; Benassi, Roseli Frederigi (Revista Hipótese, 2015)
This article presents a case study on characterization and remediation of soil contaminated with benzene in a petrol station located in urban area. The methodological procedure included the characterization of the surrounding area with respect to land use, implementation of wells to collect soil and water samples, and monitoring of the evolution of the concentration of benzene dissolved in water. Benzene concentrations were detected above the reference values in three (3) of the thirteen (13) wells established in the area, which lead to the establishment of a contingency plan that consisted in application of Multi Phase Extraction (MPE) technology to reduce the concentration of benzene at acceptable level in accordance with the current regulation.
Keywords: Benzene; Contamination; Remediation; Soil